Ederly Program Guidance as a Strategy to Empower Neglected Ederly - Elly Kuntjorowati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
In order to cope a lot of numbers of neglected elderly, the Ministry of Social Affairs has been launching a program (policy) called Neglected Elderly Social Assistance (ASLUT). The main object of ASLUT Program is to ease living burdenof neglected ederly in order to meet the basic needs and living maintenance, the second is to maintain the welfare of the elderly so they can enjoy a reasonable standard of living. To realize the goal of ASLUT program, the program then requires a guidance as a strategy. The research question is how the strategy has to be performed to mentor ASLUT program to empower neglected elderly? The purpose of the research is to know the local empirical strategy of ASLUT programguidance conducted in the empowerment of neglected elderly. The research takes place in Banjarbaru City, West Kalimantan Province. The research method used is descriptive. The result showed that the guidance is used as strategy to direct cash assistance will get assuredly to the concerned (Ederly). Guidance also serves as commitment with the post office to liquify and disburse the aid in cash, and nominating other names for replacement if the existing die and to be resumed by other ederly that is waiting in list.